The Resilience of Religious Courts and Economic Disruption: A Constitutional Law Perspective - Fitriciada Azhari, Aidul; Isman, Isman (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze how the interaction between economic disruption, internal adaptation, and constitutional legitimacy, within the framework of path dependence, shapes the resilience of the Religious Courts in Indonesian law. This study employs a qualitative-juridical research approach, incorporating historical, socio-legal, and institutional analysis methods. Data were collected from literature archives, constitutional documents, legislation, court decisions, and judicial bureaucrats. The analysis used pattern-tracking techniques and circular causal models, based on Lev (1978) and Manan (2003), to identify the relationships among external pressures, adaptation mechanisms, and institutional stability. The results show that judicial resilience does not stem solely from constitutional norms, but from the ability of institutions to transduce economic pressures into new institutional legitimacy through ambivalent adaptation—both defensive and innovative. Digital disruption expands the space for substantive legitimacy, but also produces structural noise that weakens judicial independence. The novelty of this research lies in the construction of the constitutional-resilience cycle, a nonlinear model that explains how constitutional legitimacy functions as both an amplifier and a regressive filter in absorbing economic disruption, resulting in a dynamic pattern of resilience that classical path-dependence theory cannot explain.